A method for preparing an alkali-slag internal curing material, concrete
Patent Information
- Application Number
- CN202611058838.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-23
AI Technical Summary
该技术虽能保持28d抗压强度不降低并降低自收缩,但仍存在以下局限:(1)采用纯碱渣,未能利用粉煤灰等活性掺合料的化学改性作用,纯碱渣单独粉磨时易发生“包球”现象,粉磨效率低;(2)需附加水,改变了混凝土的实际水胶比且研究表明附加水对混凝土力学性能存在不利影响;(3)仅适用于超高性能混凝土的自收缩,不适用于改善普通混凝土和高性能混凝土的干燥收缩及抗冻融性能(超高性能混凝土的自收缩是由于极低水胶比下内部自干燥导致;而普通混凝土和高性能混凝土的干燥收缩是由于外部环境失水导致,与超高性能混凝土的自收缩的机理并不相同,因此,适用于超高性能混凝土的自收缩,不适用于改善普通混凝土和高性能混凝土的干燥收缩及抗冻融性能)
固废高值化:成功将大宗工业固废碱渣转化为高附加值的功能性建筑材料,解决了其处置难题,环保效益显著。
Smart Images

Figure CN122958087A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of solid waste resource utilization and building materials, specifically to a method for preparing an alkaline slag internal curing material and concrete. Background Technology
[0002] High-performance concrete (HPC) is widely used due to its high strength and durability. However, its low water-cement ratio and high cementitious material content lead to increased autogenous shrinkage and drying shrinkage, making it prone to early cracking and severely affecting its long-term durability and service life. While ordinary concrete also has a high water-cement ratio, it also exhibits significant drying shrinkage in dry environments, impacting its long-term durability. Internal curing technology is an effective solution to this problem. It introduces materials that can retain water and continuously release it during cement hydration, providing additional moisture for cement hydration and effectively inhibiting shrinkage.
[0003] The ammonia-soda process generates a large amount of alkaline slag solid waste, mainly composed of CaCO3, CaCl2, CaSO4, and a small amount of NaOH. Due to its high chloride ion content and strong alkalinity, it is difficult to dispose of and long-term stockpiling seriously pollutes the environment. Existing technologies have attempted to utilize alkaline slag as an internal curing material: after dechlorination, dispersing, and drying, the soda ash slag is ground into powder using a cutting tool or grinding disc and used as an internal curing agent to replace silica fume in ultra-high performance concrete by mass. However, when using this material, 30-60% water by mass of the powder is required. Although this technology can maintain the 28-day compressive strength and reduce autogenous shrinkage, it still has the following limitations: (1) It uses soda ash residue and fails to utilize the chemical modification effect of active admixtures such as fly ash. When soda ash residue is ground alone, it is easy to cause "balling" phenomenon, resulting in low grinding efficiency; (2) It requires additional water, which changes the actual water-cement ratio of the concrete, and studies have shown that additional water has an adverse effect on the mechanical properties of concrete; (3) It is only applicable to the autogenous shrinkage of ultra-high performance concrete and not applicable to improving the drying shrinkage and freeze-thaw resistance of ordinary concrete and high performance concrete. (The autogenous shrinkage of ultra-high performance concrete is caused by internal self-drying under extremely low water-cement ratio; while the drying shrinkage of ordinary concrete and high performance concrete is caused by water loss from the external environment. The mechanism of autogenous shrinkage is different from that of ultra-high performance concrete. Therefore, it is applicable to the autogenous shrinkage of ultra-high performance concrete and not applicable to improving the drying shrinkage and freeze-thaw resistance of ordinary concrete and high performance concrete.) Summary of the Invention
[0004] This invention provides a method for preparing an internal curing material for alkali slag and concrete. This invention can efficiently utilize alkali slag solid waste, and the prepared internal curing material for alkali slag can improve the mechanical properties of concrete as well as the drying shrinkage and freeze-thaw resistance of ultra-high performance concrete, ordinary concrete and high performance concrete.
[0005] This invention provides a method for preparing an internal curing material for alkali slag, comprising the following steps: The alkaline residue is mixed with water to remove chlorine, resulting in dechlorinated alkaline residue. The dechlorinated alkali residue is mixed with fly ash and then dry ball milled to obtain the internal curing material of the alkali residue. The dry ball milling time is greater than 1 minute and less than 4 minutes.
[0006] Preferably, by mass fraction, the alkali residue comprises 48.7% CaO, 41.91% Cl, 12.40% SiO2, 10.87% MgO, 6.49% SO3, 3.43% Al2O3, 1.39% Fe2O3 and 0.30% K2O.
[0007] Preferably, the mass ratio of the alkali residue to water is 1:8~10.
[0008] Preferably, the dechlorination process includes: allowing the mixture obtained by mixing alkaline residue and water to stand, filtering, and then drying the resulting filter residue; the drying temperature is 100~110℃.
[0009] Preferably, the mass ratio of the dechlorination alkali residue to fly ash is 2~3:1.
[0010] Preferably, the mass ratio of the alkali residue to water is 1:8, so the dry ball milling time is 2 minutes, and the mass ratio of the dechlorinated alkali residue to fly ash is 2:1.
[0011] The present invention also provides a concrete, the raw materials for which preparation includes water and dry materials; The dry materials include alkali residue internal curing materials, cementing materials, sand, stone and water-reducing agents; The internal curing material for alkali slag includes the internal curing material for alkali slag prepared by the preparation method described in the above technical solution.
[0012] Preferably, the mass of the curing material inside the alkali slag is 5-15% of the mass of the cementitious material; the cementitious material includes one or more of cement, fly ash, slag powder and silica fume.
[0013] Preferably, by weight, the dry material comprises 25-50 parts of alkali slag internal curing material, 300-500 parts of cement, 75-100 parts of fly ash, 75-100 parts of slag powder, 520-525 parts of sand, 1100-1150 parts of stone, and 4-5 parts of water-reducing agent. Alternatively, by weight, the dry material comprises 17.5-52.5 parts of alkali residue internal curing material, 240-250 parts of cement, 52.5-105 parts of fly ash, 590-595 parts of sand, and 1250-1300 parts of stone. Alternatively, by weight, the dry material includes 40-80 parts of alkali slag internal curing material, 560-600 parts of cement, 40-80 parts of fly ash, 40-80 parts of mineral powder, 80-100 parts of silica fume, 340-350 parts of fine sand, 350-360 parts of medium sand, 370-380 parts of coarse sand, and 9-10 parts of water-reducing agent.
[0014] Preferably, the water-reducing agent includes a polycarboxylate high-performance water-reducing agent.
[0015] Compared with the prior art, the advantages of the present invention are: High-value utilization of solid waste: The bulk industrial solid waste alkali slag has been successfully transformed into high-value-added functional building materials, solving its disposal problem and achieving significant environmental benefits.
[0016] The process is innovative and simple: It employs a combined process of "water washing for dechlorination + fly ash synergistic grinding," utilizing the "solid lubrication" and "dispersion" effects of fly ash microspheres to effectively solve the severe "ball encapsulation" problem encountered when dry ball milling of alkali slag alone, thus improving grinding efficiency. Compared to wet ball milling, the dry process produces no wastewater and requires no subsequent drying. Compared to grinding soda ash slag alone, the material of this invention exhibits better workability, and the pozzolanic activity of fly ash can participate in the hydration reaction. Furthermore, it eliminates the cumbersome step of pre-saturating the internal curing materials of traditional alkali slag, resulting in a simple preparation process, low cost, and ease of industrial production.
[0017] Dual benefits: The material of this invention not only has a physical internal conditioning effect (absorption-release of water), but also contains Ca... 2+ OH - SO4 2- Plasma can also participate in hydration reactions, optimizing the morphology and pore structure of hydration products, thus achieving a chemical modification effect.
[0018] Significantly Improved Durability: Shrinkage Inhibition: Through continuous internal water supply, the drying shrinkage value of concrete is significantly reduced. At a 10% admixture in ordinary concrete, the 7-day shrinkage value is reduced by more than 80% compared to the baseline group; at a 10% admixture in high-performance concrete, the 7-day shrinkage value is reduced by more than 60%; and at an 8% admixture in ultra-high-performance concrete, the 7-day shrinkage value is reduced by more than 65%.
[0019] Enhanced freeze-thaw resistance: The refinement of internal pores and the filling effect of unhydrated particles reduce the content of harmful pores, significantly improving the freeze-thaw cycle resistance of concrete. At a 10% admixture in ordinary concrete, the mass loss rate is reduced by 41.5% after 75 freeze-thaw cycles; at a 10% admixture in high-performance concrete, the mass loss rate is reduced by 51.4% after 300 freeze-thaw cycles.
[0020] It is economical and practical: the raw material cost is extremely low, the preparation process is simple, no complicated equipment or high-temperature calcination is required, and it is easy to carry out industrial production and large-scale engineering applications.
[0021] This invention utilizes the pozzolanic activity of fly ash to achieve a dual effect of physical internal curing and chemical modification. The prepared alkali-slag internal curing material is directly incorporated into concrete in dry powder form, automatically saturating with mixing water without the need for additional internal curing water. Compared with existing alkali-slag internal curing technologies that require additional water, this invention avoids the alteration of the actual water-cement ratio of concrete and its adverse effects on compressive strength caused by additional water. Experimental results show that, under the same alkali-slag dosage (10%), the 7-day and 14-day compressive strength of ordinary concrete without additional water is increased by 12.9% and 22.9% respectively compared to the baseline group; however, when the proportion of additional water increases to 12.5% and 25%, the compressive strength of ordinary concrete decreases to varying degrees, and the higher the proportion of additional water, the more significant the strength deterioration.
[0022] Furthermore, by optimizing the dechlorination water-to-solid ratio (8:1), the mass ratio of alkali residue to fly ash (2:1), and the grinding time (2 min), and combining it with a dry ball milling process, direct mixing of dry powder, and a method of use without the need for additional water, this invention effectively improves the workability, compressive strength, and freeze-thaw resistance of concrete, while significantly inhibiting the drying shrinkage of concrete. Attached Figure Description
[0023] Figure 1 This is a flowchart illustrating the preparation process of the internal curing material for alkali slag in Example 1; Figure 2 This is a SEM image of the internal curing material for alkali residue prepared in Example 1. Detailed Implementation
[0024] This invention provides a method for preparing an internal curing material for alkali slag, comprising the following steps: The alkaline residue is mixed with water to remove chlorine, resulting in dechlorinated alkaline residue. The dechlorinated alkali residue is mixed with fly ash and then dry ball milled to obtain the internal curing material of the alkali residue. The dry ball milling time is greater than 1 minute and less than 4 minutes.
[0025] This invention involves mixing alkaline residue with water to remove chlorine, resulting in dechlorinated alkaline residue.
[0026] In this invention, the preferred mass ratio of alkaline slag to water is 1:8 to 10, and in a specific embodiment, it can be 1:9. If the water-to-solid ratio is too low, chloride ions will not dissolve sufficiently, resulting in poor dechlorination; if the water-to-solid ratio is too high, although the dechlorination effect is good, the water consumption is large, the drying energy consumption is high, and it may lead to the loss of some active components in the alkaline slag. The 28-day strength activity index of the curing material obtained with an alkaline slag mass ratio of 1:8 is 63%, while it is only 34% with a water-to-solid ratio of 10:1. This proves that moderate water washing can retain the calcium-based active components of the alkaline slag, avoiding excessive water washing that leads to activity loss, thereby ensuring the compressive strength of subsequent concrete.
[0027] In this invention, the alkali residue preferably comprises, by mass fraction, 48.7% CaO, 41.91% Cl, 12.40% SiO2, 10.87% MgO, 6.49% SO3, 33.43% Al2O3, 1.39% Fe2O3 and 0.30% K2O.
[0028] In this invention, the dechlorination preferably includes: allowing the mixture obtained by mixing alkaline residue and water to stand, filtering, and then drying the resulting filter residue.
[0029] In this invention, the mixing is preferably carried out under mechanical stirring conditions, and the mechanical stirring time is preferably 10-30 minutes, which can be 15 minutes, 20 minutes, or 25 minutes in specific embodiments of this invention. Mechanical stirring can fully mix and disperse the alkali residue and water, promoting the dissolution of soluble salts.
[0030] In this invention, the settling time is preferably 12-24 hours, and in specific embodiments of this invention, it can be 15 hours, 18 hours, 20 hours, or 22 hours. A settling time within the above range allows for sufficient solid-liquid separation.
[0031] In this invention, the drying temperature is preferably 100~110℃. There is no specific limitation on the drying time; drying to constant weight is sufficient. The drying temperature should not be too high to prevent the dehydration of the gypsum dihydrate (CaSO4·2H2O) in the alkali residue, which would affect its subsequent expansion compensation effect in concrete.
[0032] After obtaining the dechlorination-alkali slag, the present invention mixes the dechlorination-alkali slag with fly ash and performs dry ball milling to obtain the internal curing material of the alkali slag.
[0033] In this invention, the preferred mass ratio of the dechlorinated alkali residue to fly ash is 2-3:1, and the preferred fly ash is secondary fly ash. The introduction of fly ash plays a crucial role in aiding grinding. When alkali residue is ground alone, due to the van der Waals forces between particles, a "balling" phenomenon easily occurs, where the powder coats the surface of the grinding balls, resulting in extremely low grinding efficiency. Furthermore, prolonged grinding will destroy the natural porous structure of the alkali residue. Fly ash particles are small and spherical, exhibiting excellent grinding aid properties. During the grinding process, fly ash microspheres can effectively disperse alkali residue particles, weaken the interparticle forces, thereby significantly alleviating the "balling" phenomenon and improving grinding efficiency and powder yield.
[0034] The mass ratio of dechlorination alkali slag to fly ash determines the performance balance of the composite material: too little fly ash results in poor grinding aid, and too high a proportion of alkali slag leads to low overall activity of the composite material; too much fly ash dilutes the porous internal curing effect of the alkali slag. Experiments comparing mass ratios of 2:1 and 3:1 revealed that the composite material exhibited superior performance in water absorption and release, strength activity index, and flowability at a mass ratio of 2:1. Specifically, the 28-day strength activity index (tested according to GB / T1596-2017) of the 2:1 ratio material was 63%, higher than the 49% of the 3:1 ratio; the mortar flowability was 147 mm, also better than the 141 mm of the 3:1 ratio. Therefore, the optimal mass ratio of dechlorination alkali slag to fly ash is 2:1, solving the performance degradation problem caused by improper proportioning in existing technologies.
[0035] In this invention, the dry ball milling time is greater than 1 minute and less than 4 minutes, and in specific embodiments of this invention, it can be 2 minutes or 3 minutes. The grinding time directly affects particle fineness, morphology, and pore structure. If the time is too short (e.g., 1 minute), the particles are not sufficiently broken down, resulting in an excessively large average particle size (approximately 39 μm), a small specific surface area, and low internal curing efficiency. If the time is too long (e.g., 4 minutes), although the particles are finer (average particle size approximately 26 μm), excessive grinding will destroy the original porous structure of the alkali slag, leading to a decrease in its water absorption capacity and an increase in the water demand of the powder, which is detrimental to the workability of concrete. Experiments show that when the grinding time is 2 minutes, the average particle size of the material is approximately 38 μm, the D50 is approximately 35 μm, the particle size distribution is reasonable, and the necessary pore structure of the alkali slag is preserved, taking into account both good water absorption and release characteristics and mechanical properties.
[0036] In this invention, the rotational speed of the dry ball mill is preferably 50 r / min, and the diameter of the grinding balls used in the dry ball mill is preferably 16 mm, 23 mm, 10 mm, and 8 mm; the number of grinding balls with a diameter of 16 mm is preferably 19, the number of grinding balls with a diameter of 14 mm is preferably 23, the number of grinding balls with a diameter of 10 mm is preferably 42, and the number of grinding balls with a diameter of 8 mm is preferably 56.
[0037] The preferred ratio of the mass of the grinding balls to the total mass of the dechlorination alkali slag and fly ash during dry ball milling is 1:1.
[0038] In this invention, no additional water or liquid grinding aid is added to the ball mill during the dry ball milling process.
[0039] After grinding, the present invention preferably further includes passing the material through a 200-mesh sieve.
[0040] In this invention, the average particle size of the internal curing material for alkali residue is preferably 33.44~43.49 μm, D 10 Preferably, the micrometer diameter is 10.45~12.68 μm, and the micrometer diameter is D. 50 Preferably, the micrometer diameter is 30.93~38.33 μm, D 90 The preferred size is 58.87~82.28μm.
[0041] The alkali slag internal curing material prepared by this invention has good water absorption-storage-release properties, and can be directly added to concrete in dry powder form without pre-absorption or additional mixing water. During use, the material automatically saturates with the concrete mixing water and gradually releases water as the internal humidity decreases due to cement hydration, thus exerting its internal curing effect. Compared with existing internal curing agents that require the addition of 30%–60% water, this invention simplifies the construction ratio and avoids the adverse effects of additional water on the actual water-cement ratio of concrete and its compressive strength. Comparative tests show that, under the same alkali slag dosage (10%), the 7-day and 14-day compressive strength of ordinary concrete without additional water is increased by 12.9% and 22.9% respectively compared to the baseline group; however, when the proportion of added water increases to 12.5% and 25%, the compressive strength of the concrete decreases to varying degrees, and the higher the proportion of added water, the more obvious the strength deterioration. This indicates that the dry mixing method adopted in this invention is not only simple to operate but also more conducive to the development of mechanical properties.
[0042] The present invention also provides a concrete, the raw materials for which preparation includes water and dry materials; The dry materials include alkali slag internal curing materials, cement, fly ash, slag powder, sand, stone and water-reducing agent; The internal curing material for alkali slag includes the internal curing material for alkali slag prepared by the preparation method described in the above technical solution.
[0043] By weight, the dry material preferably includes 25-50 parts of alkali slag internal curing material, 300-500 parts of cement, 75-100 parts of fly ash, 75-100 parts of slag powder, 520-525 parts of sand, 1100-1150 parts of stone and 4-5 parts of water-reducing agent. Alternatively, by weight, the dry material comprises 17.5-52.5 parts of alkali residue internal curing material, 240-250 parts of cement, 52.5-105 parts of fly ash, 590-595 parts of sand, and 1250-1300 parts of stone. Alternatively, by weight, the dry material includes 40-80 parts of alkali slag internal curing material, 560-600 parts of cement, 40-80 parts of fly ash, 40-80 parts of mineral powder, 80-100 parts of silica fume, 340-350 parts of fine sand, 350-360 parts of medium sand, 370-380 parts of coarse sand, and 9-10 parts of water-reducing agent.
[0044] In this invention, the mass of the internal curing material in the alkali slag is preferably 5-15% of the mass of the cementitious material, and the cementitious material preferably includes one or more of cement, fly ash, slag powder, and silica fume. When the water-cement ratio is 0.3 (i.e., high-performance concrete), the mass of the internal curing material in the alkali slag is preferably 5-10% of the mass of cement; when the water-cement ratio is 0.5 (i.e., ordinary concrete), the mass of the internal curing material in the alkali slag is preferably 5-15% of the mass of cement; when the water-cement ratio is 0.2 (i.e., ultra-high-performance concrete), the mass of the internal curing material in the alkali slag is preferably 5-8% of the mass of cement. If the dosage of the internal curing material in the alkali slag is too low, the internal curing effect is not obvious; if the dosage is too high, the additional porosity effect caused by the porous nature of the alkali slag will weaken the improvement effect.
[0045] In this invention, the water-reducing agent preferably includes a polycarboxylate high-performance water-reducing agent.
[0046] The following detailed description, in conjunction with embodiments, illustrates the preparation method of the alkaline slag internal curing material and the concrete provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0047] The following are some of the raw material parameters used in the embodiments and comparative examples of this invention: Raw alkaline residue: provided by Tangshan Sanyou Chemical Co., Ltd., light grayish-white lumpy wet residue, with a moisture content of 32-52%, and the main chemical components are CaO 48.7%, Cl 41.91%, SiO2 12.40%, MgO 10.87%, SO3 6.49%, Al2O3 3.43%, Fe2O3 1.39%, K2O 0.30%; Fly ash: Grade II ash, 28.3% residue on a 45μm square mesh sieve, water requirement ratio 102%, loss on ignition 7.4%; Cement: P·O 42.5 grade ordinary Portland cement; Mineral powder: S95 grade granulated blast furnace slag powder, specific surface area 423 m² 2 / kg, 28d activity index 97.5%; Silica fume: SiO2 content 92%; Sand: Natural river sand, medium sand of Zone II, fineness modulus 2.48; Stone: 5~20mm continuously graded crushed stone; Water-reducing agent: Polycarboxylate high-performance water-reducing agent, water reduction rate 27%, solid content 38.3%; Fine sand: fineness modulus 0.52; Medium sand: fineness modulus 1.73; Coarse sand: fineness modulus 3.05; Silica fume: SiO2 content 92%.
[0048] Figure 1 This is a flowchart illustrating the preparation process of the internal curing material for alkali slag in Example 1.
[0049] Example 1 By weight percentage, 66.7% of the alkaline slag powder and 33.3% of the fly ash that have undergone water washing and dechlorination treatment are weighed as raw materials.
[0050] The preparation method is as follows: (1) Water washing to remove chlorine: Mix the original alkali residue with water at a water-to-solid mass ratio of 8:1, stir mechanically for 20 minutes, let stand for 24 hours, remove the supernatant, and dry the filter residue at 105℃ to constant weight to obtain chlorine-removed alkali residue. (2) Co-grinding: The above-mentioned dechlorination alkali slag and fly ash are mixed at a mass ratio of 2:1 and added to the Licheng Technology LC-PBM-6L vertical planetary ball mill. They are ground together at a speed of 50 r / min for 2 min (the diameter and amount of grinding balls used in the ball mill are: 19 large balls 16mm, 23 medium balls 14mm, 42 medium and small balls 10mm, and 56 small balls 8mm; the ball-to-material ratio is 1:1). The mixture is then passed through a 200-mesh standard sieve to obtain the alkali slag internal curing material.
[0051] The particle size characteristics of the material obtained in this embodiment are: average particle size 37.70 μm, D 10 It is 12.68 μm, D 50 It is 34.86 μm, D 90 The thickness is 66.40 μm. The water absorption rate, tested using the tea bag method, is 125%. Under conditions of 43% relative humidity controlled by a saturated K₂CO₃ solution, the water release rate is slow and stable. According to GB / T 1596-2017 testing standards, the 28-day strength activity index is 63%, and the mortar flowability is 147 mm.
[0052] Figure 2 This is a SEM image of the internal curing material for alkali residue prepared in Example 1.
[0053] Depend on Figure 2 It can be seen that the loose agglomerated structure of the alkali residue is broken up and forms a uniform composite particle structure with the spherical fly ash.
[0054] Example 2: Preparation of curing material for alkali slag (water-to-solid ratio 8:1, mass ratio of alkali slag to fly ash 3:1) Weigh out 75% of the alkaline slag powder and 25% of the fly ash that have been treated by water washing and dechlorination as raw materials, by weight percentage.
[0055] The preparation method is as follows: (1) Water washing to remove chlorine: Mix the original alkali residue with water at a water-to-solid mass ratio of 8:1, stir mechanically for 20 minutes, let stand for 24 hours, remove the supernatant, and dry the filter residue at 105℃ to constant weight to obtain chlorine-removed alkali residue. (2) Co-grinding: The above-mentioned dechlorination alkali slag and fly ash are mixed at a mass ratio of 3:1 and added to the Licheng Technology LC-PBM-6L vertical planetary ball mill for 2 minutes at a speed of 50 r / min (the diameter and amount of grinding balls used in the ball mill are: 19 large balls 16mm, 23 medium balls 14mm, 42 medium and small balls 10mm, and 56 small balls 8mm; the ball-to-material ratio is 1:1). The mixture is then passed through a 200-mesh standard sieve to obtain the alkali slag internal curing material.
[0056] The particle size characteristics of the material obtained in this embodiment are: average particle size 43.49 μm, D 10 It is 11.57 μm, D 50 It is 38.33 μm, D 90 The thickness is 82.28 μm. According to GB / T 1596-2017, the 28-day strength activity index is 49%, and the mortar flowability is 141 mm.
[0057] Example 3: Preparation of curing material for alkali slag (water-to-solid ratio 10:1, alkali slag to fly ash mass ratio 2:1) By weight percentage, 66.7% of the alkaline slag powder and 33.3% of the fly ash that have undergone water washing and dechlorination treatment are weighed as raw materials.
[0058] The preparation method is as follows: (1) Water washing to remove chlorine: The original alkali residue is mixed with water at a water-to-solid mass ratio of 10:1, mechanically stirred for 20 minutes, and allowed to stand for 24 hours. The supernatant is then removed, and the filter residue is dried at 105℃ to constant weight to obtain dechlorinated alkali residue. (2) Co-grinding: The above-mentioned dechlorination alkali slag and fly ash are mixed at a mass ratio of 2:1 and added to the Licheng Technology LC-PBM-6L vertical planetary ball mill. They are ground together at a speed of 50 r / min for 2 min (the diameter and amount of grinding balls used in the ball mill are: 19 large balls 16mm, 23 medium balls 14mm, 42 medium and small balls 10mm, and 56 small balls 8mm; the ball-to-material ratio is 1:1). The mixture is then passed through a 200-mesh standard sieve to obtain the alkali slag internal curing material.
[0059] The particle size characteristics of the material obtained in this embodiment are: average particle size 33.44 μm, D 10 It is 11.27 μm, D 50 It is 30.93 μm, D 90 The thickness is 58.87 μm. According to GB / T 1596-2017, the 28-day activity index is 34%.
[0060] Example 4: Preparation of curing material for alkali slag (water-to-solid ratio 10:1, alkali slag to fly ash mass ratio 3:1) Weigh out 75% of the alkaline slag powder and 25% of the fly ash that have been treated by water washing and dechlorination as raw materials, by weight percentage.
[0061] The preparation method is as follows: (1) Water washing to remove chlorine: The original alkali residue is mixed with water at a water-to-solid mass ratio of 10:1, mechanically stirred for 20 minutes, and allowed to stand for 24 hours. The supernatant is then removed, and the filter residue is dried at 105℃ to constant weight to obtain dechlorinated alkali residue. (2) Co-grinding: The above-mentioned dechlorination alkali slag and fly ash are mixed at a mass ratio of 3:1 and added to the Licheng Technology LC-PBM-6L vertical planetary ball mill for 2 minutes at a speed of 50 r / min (the diameter and amount of grinding balls used in the ball mill are: 19 large balls 16mm, 23 medium balls 14mm, 42 medium and small balls 10mm, and 56 small balls 8mm; the ball-to-material ratio is 1:1). The mixture is then passed through a 200-mesh standard sieve to obtain the alkali slag internal curing material.
[0062] The particle size characteristics of the material obtained in this embodiment are: average particle size 36.82 μm, D 10 It is 10.45 μm, D 50 It is 32.91 μm, D 90 The thickness is 68.38 μm. According to GB / T 1596-2017, the 28-day activity index is 23%.
[0063] Comparative Example 1: Untreated alkaline residue (raw alkaline residue to fly ash mass ratio 2:1) The difference from Example 1 is that the water washing treatment in step (1) is not performed, and the dried original alkaline residue is directly mixed with fly ash and then ground together.
[0064] The material obtained in this comparative example had a water release rate of only 14% after 10 days, far lower than that of Example 1. This is because the undisturbed alkali slag contains a large amount of soluble salts in its pores. When the ambient humidity decreases, these salts crystallize and precipitate, physically blocking the water migration pathways and severely restricting water release. Therefore, this material is not suitable for use as an internal curing material for concrete alkali slag.
[0065] Comparative Example 2: Untreated alkaline residue (raw alkaline residue to fly ash mass ratio 3:1) The difference from Example 2 is that the water washing treatment in step (1) is not performed, and the dried original alkaline residue is directly mixed with fly ash and then ground together.
[0066] The material obtained in this comparative example also had an extremely low water release rate after 10 days, further confirming that regardless of the ratio of alkali residue to fly ash, unwashed undisturbed alkali residue is not suitable as an internal curing material for concrete.
[0067] Comparative Example 3 had too short a grinding time (water-to-solid ratio 8:1, alkali residue to fly ash mass ratio 2:1, grinding time 1 min). The difference from Example 1 is that the co-grinding time in step (2) is adjusted to 1 min.
[0068] The particle size characteristics of the material obtained in this comparative example are: average particle size 39.33 μm, D 10 It is 10.77 μm, D50 is 34.89 μm, D 90 The particle size was 73.80 μm. SEM observation showed that there were still many large agglomerated particles, indicating insufficient particle breakage. The 28-day strength activity index was only 36%, significantly lower than that of Example 1 (63%); the mortar flowability was 137 mm, also lower than that of Example 1 (147 mm). The excessively short grinding time resulted in coarse particles, insufficient powder dispersion, and low internal curing efficiency.
[0069] Comparative Example 4: Grinding time was too long (water-to-solid ratio 8:1, alkali residue to fly ash mass ratio 2:1, grinding time 4 min). The difference from Example 1 is that the co-grinding time in step (2) is adjusted to 4 min.
[0070] The particle size characteristics of the material obtained in this comparative example are: average particle size 26.38 μm, D 10 It is 7.72 μm, D 50 It is 23.73 μm, D 90 The particle size was 48.54 μm. SEM observation showed that although the particles were further refined, more fine particles adhered to the surface of the larger particles, and local aggregation was intensified again. The water absorption ratio decreased to 112%, and the water release rate was slow and stable. The 28-day strength activity index was 42%, which was significantly lower than that of Example 1.
[0071] Comparative Example 5 had too short a grinding time (water-to-solid ratio 8:1, alkali residue to fly ash mass ratio 3:1, grinding time 1 min). The difference from Example 2 is that the co-grinding time in step (2) is adjusted to 1 min.
[0072] The particle size characteristics of the material obtained in this comparative example are: average particle size 55.86 μm, D 10 It is 18.84 μm, D50 is 51.67 μm, D 90The particle size was 98.31 μm, indicating a significantly coarse particle size distribution. The 28-day strength activity index was only 26%, and the mortar flowability was 120 mm. At a 3:1 mixing ratio, the adverse effects of insufficient grinding time were even more pronounced.
[0073] Comparative Example 6: Grinding time was too long (water-to-solid ratio 8:1, alkali residue to fly ash mass ratio 3:1, grinding time 4 min). The difference from Example 2 is that the co-grinding time in step (2) is adjusted to 4 min.
[0074] The particle size characteristics of the material obtained in this comparative example are: average particle size 37.68 μm, D 10 It is 13.20 μm, D 50 It is 35.10 μm, D 90 The thickness is 65.49 μm. The 28-day strength activity index is 41%, and the mortar flowability is 128 mm. Compared with Example 1, even with optimized grinding time (4 min), the overall performance is still inferior to Example 1 when deviating from the optimal ratio (3:1 instead of 2:1).
[0075] Table 1. Preparation parameters and main performance indicators of each embodiment and comparative example.
[0076] Table 1 shows that the alkali slag internal curing material prepared in Example 1 has the best overall performance in terms of water absorption and release, strength and activity, and fluidity. Comparative Examples 1-2, due to the lack of water washing, have extremely low water release rates and are unsuitable as alkali slag internal curing materials. Comparative Examples 3 and 5 have coarse particles and low strength and activity due to excessively short grinding times. Comparative Examples 4 and 6 have pore structure damage, reduced water absorption and release performance, and decreased strength and activity due to excessively long grinding times. These results fully demonstrate that water washing for dechlorination is a necessary step in preparing qualified alkali slag internal curing materials; a grinding time of 2 minutes is the optimal parameter for achieving the best balance between particle refinement and pore structure protection; and a 2:1 mass ratio of alkali slag to fly ash is the optimal proportion for overall performance.
[0077] Test Example 1: Performance Verification in High-Performance Concrete According to Table 2, two sets of reference HCC with the same mix proportion and two sets of high-performance concrete HCT2 with the same mix proportion of the alkali-added slag internal curing material described in Example 1 were prepared respectively (among the two sets of HCC with the same mix proportion, one set was used to measure the 7-day compressive strength and the other set was used to measure the 28-day compressive strength; the two sets of HCT2 with the same mix proportion were prepared in the same way). The above four sets of high-performance concrete were cured in a standard curing room (temperature 20±2℃, relative humidity ≥95%), and three high-performance concrete specimens were formed from each set. The compressive strength of the high-performance concrete specimens of each example were tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019); the slump and spread were determined according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016); and the drying shrinkage and freeze-thaw resistance were tested according to the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2024). The test results are shown in Tables 2-5.
[0078] Table 2. HCC, raw materials and dosage of high-performance concrete for the benchmark group (kg / m³) 3 )
[0079] Table 3. Test results of workability and mechanical properties of HCC and high-performance concrete in the benchmark group.
[0080] Table 4. Drying shrinkage test results of HCC and high-performance concrete in the benchmark group (×10) -6 )
[0081] Table 5. Test results of the freeze-thaw resistance of HCC and high-performance concrete after 300 freeze-thaw cycles (benchmark group).
[0082] As shown in Table 3, after incorporating the alkaline slag curing material of this invention, the slump of the high-performance concrete was 263 mm, which increased rather than decreased, indicating that its workability was not a problem; the spread was 505 mm, basically the same as the benchmark group, and the fluidity did not decrease significantly; the 28-day compressive strength was 63.39 MPa, reaching 96.4% of the benchmark group, and the compressive strength did not decrease significantly, falling within the normal dispersion range of concrete tests. As shown in Table 4, the 7-day shrinkage value of the high-performance concrete incorporating the alkaline slag curing material was only 74.3 × 10⁻⁶. -6Compared to the baseline group, the shrinkage rate was reduced by 61.4%, demonstrating a significant shrinkage inhibition effect. As shown in Table 5, after 300 freeze-thaw cycles, the mass loss rate of the high-performance concrete incorporating alkali-slag curing material was only 0.67%, a decrease of 51.4% compared to the baseline group; the relative dynamic modulus of elasticity remained at 70.7%, an increase of 9.1% compared to the baseline group.
[0083] The performance of the alkaline slag internal curing material of this invention in ordinary concrete and ultra-high performance concrete was verified by referring to the above test methods.
[0084] Test Example 2: Performance Verification in Ordinary Concrete According to Table 6, two sets of reference PCC with the same mix proportion and two sets of ordinary concrete PCT2 with the same mix proportion were prepared respectively (one set of PCC with the same mix proportion was used to measure 7-day compressive strength, and the other set was used to measure 28-day compressive strength; the two sets of PCT2 with the same mix proportion were prepared in the same way). The above four sets of high-performance concrete were cured in a standard curing room (temperature 20±2℃, relative humidity ≥95%), and three high-performance concrete specimens were obtained from each set. The compressive strength of the high-performance concrete specimens of each embodiment were tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019); the slump and spread were determined according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016); and the drying shrinkage and freeze-thaw resistance were tested according to the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2024). The test results are shown in Tables 6-9.
[0085] Table 6. Raw materials and dosage of PCC and PCT2 (kg / m³) 3 )
[0086] Table 7 Test results of working and mechanical properties of PCC and PCT2
[0087] Table 8 Results of drying shrinkage tests for PCC and PCT2 (×10) -6 )
[0088] Table 9. Results of antifreeze performance tests of PCC and PCT2 after 75 freeze-thaw cycles.
[0089] As shown in Table 7, after incorporating the alkaline slag curing material of this invention, the slump of ordinary concrete was 158 mm and the spread was 272 mm, improving both slump and spread. The 28-day compressive strength was 27.42 MPa, reaching 93.4% of the baseline group, with no significant decrease in compressive strength. As shown in Table 8, the 7-day shrinkage value of the high-performance concrete incorporating the alkaline slag curing material was only 31.1 × 10⁻⁶ MPa. -6 Compared to the baseline group, the shrinkage rate was reduced by 89.8%, demonstrating a significant shrinkage inhibition effect. As shown in Table 9, after 75 freeze-thaw cycles, the mass loss rate of high-performance concrete with alkali slag internal curing material was only 3.1%, a decrease of 41.5% compared to the baseline group; the relative dynamic modulus of elasticity remained at 91.2%, an increase of 11.7% compared to the baseline group.
[0090] Test Example 3: Performance Verification in Ultra-High Performance Concrete According to Table 10, two sets of reference UPCC with the same mix proportion and two sets of ultra-high performance concrete UPCT2 with the same mix proportion were prepared respectively (one set of UPCC with the same mix proportion was used to measure 7-day compressive strength, and the other set was used to measure 28-day compressive strength; the two sets of UPCT2 with the same mix proportion were prepared in the same way). The above four sets of high performance concrete were cured in a standard curing room (temperature 20±2℃, relative humidity ≥95%), and three high performance concrete specimens were obtained from each set. The compressive strength of the high performance concrete specimens of each embodiment were tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019); the slump and spread were determined according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016); and the drying shrinkage and freeze-thaw resistance were tested according to the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2024). The test results are shown in Tables 10-13.
[0091] Table 10 Raw materials and dosage of UPCC and UPCT2 (kg / m³) 3 )
[0092] Table 11 Test results of working performance and mechanical properties of UPCC and UPCT2
[0093] Table 12 Drying shrinkage test results of UPCC and UPCT2 (×10) -6 )
[0094] Table 13 Results of freeze-thaw resistance tests after 2300 freeze-thaw cycles for UPCC and UPCT
[0095] As shown in Table 11, after incorporating the alkaline slag curing material of this invention, the slump of the ultra-high performance concrete was 116 mm, and the spread was 276 mm, which were basically the same as the benchmark group, and the fluidity was not significantly reduced; the 28-day compressive strength was 78.82 MPa, reaching 90.5% of the benchmark group, and the compressive strength was not significantly reduced. As shown in Table 12, the 7-day shrinkage value of the high-performance concrete incorporating the alkaline slag curing material was only 141.6 × 10⁻⁶. -6 Compared to the baseline group, the shrinkage rate was reduced by 67.6%, demonstrating a significant shrinkage inhibition effect. As shown in Table 13, after 300 freeze-thaw cycles, the mass loss rate of the high-performance concrete incorporating alkali-slag curing material was only 0.67%, a reduction of 69.0% compared to the baseline group; the relative dynamic modulus of elasticity remained at 75.2%, an increase of 3.9% compared to the baseline group.
[0096] In summary, the alkali slag internal curing material of this invention can effectively inhibit drying shrinkage and significantly improve freeze-thaw resistance in ordinary concrete, high-performance concrete, and ultra-high-performance concrete while maintaining workability and compressive strength, thus having wide applicability.
[0097] Based on the above embodiments and comparative examples, it can be seen that: (1) This invention successfully prepared a high-performance alkaline slag internal curing material through a combined process of water washing for dechlorination and fly ash synergistic grinding. Comparative Examples 1-2 demonstrate that water washing is a necessary step to ensure the water release performance of the material; Comparative Examples 3-6 systematically verified the scientific validity and necessity of the optimal process parameters of this invention (water-to-solid ratio 8:1, mass ratio of alkaline slag to fly ash 2:1, grinding time 2 min) from different proportions and grinding time dimensions.
[0098] (2) This invention successfully solves the problem of decreased workability and compressive strength caused by co-grinding of alkali slag and fly ash in existing technologies by optimizing the dechlorination water-to-solid ratio (8:1), controlling the mass ratio of alkali slag to fly ash (2:1), and using the method of direct addition of dry powder without the need for additional water. In high-performance concrete (10% admixture), the alkali slag internal curing material of this invention makes the concrete slump basically the same as the benchmark group, and the 28-day compressive strength retention rate reaches 96.4%. Without reducing workability and compressive strength, it simultaneously achieves the dual technical effects of reducing drying shrinkage by 61.4% and reducing mass loss rate by 51.4% after 300 freeze-thaw cycles. In ordinary concrete (10% admixture) and ultra-high performance concrete (8% admixture), the same workability and compressive strength retention are achieved, and the drying shrinkage inhibition rate and freeze-thaw resistance improvement rate both reach the expected effect, which has outstanding engineering application value.
[0099] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing an internal curing material for alkali slag, characterized in that, Includes the following steps: The alkaline residue is mixed with water to remove chlorine, resulting in dechlorinated alkaline residue. The dechlorinated alkali residue is mixed with fly ash and then dry ball milled to obtain the internal curing material of the alkali residue. The dry ball milling time is greater than 1 minute and less than 4 minutes.
2. The preparation method according to claim 1, characterized in that, The alkali residue comprises, by mass fraction, 48.7% CaO, 41.91% Cl, 12.40% SiO2, 10.87% MgO, 6.49% SO3, 3.43% Al2O3, 1.39% Fe2O3 and 0.30% K2O.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of the alkaline residue to water is 1:8~10.
4. The preparation method according to claim 1, characterized in that, The dechlorination process includes: allowing the mixture obtained by mixing alkaline residue and water to stand, filtering, and then drying the resulting filter residue; the drying temperature is 100~110℃.
5. The preparation method according to claim 1, characterized in that, The mass ratio of the dechlorination alkali residue to fly ash is 2~3:
1.
6. The preparation method according to claim 1, characterized in that, The mass ratio of the alkali residue to water is 1:8, so the dry ball milling time is 2 minutes, and the mass ratio of the dechlorinated alkali residue to fly ash is 2:
1.
7. A type of concrete, characterized in that, The raw materials for preparation include water and dry materials; The dry materials include alkali residue internal curing materials, cementing materials, sand, stone and water-reducing agents; The internal curing material for alkali slag includes the internal curing material for alkali slag prepared by the preparation method according to any one of claims 1 to 6.
8. The concrete according to claim 7, characterized in that, The mass of the curing material inside the alkali slag is 5-15% of the mass of the cementitious material; the cementitious material includes one or more of cement, fly ash, slag powder and silica fume.
9. The concrete according to claim 8, characterized in that, By weight, the dry material comprises 25-50 parts of alkali slag internal curing material, 300-500 parts of cement, 75-100 parts of fly ash, 75-100 parts of slag powder, 520-525 parts of sand, 1100-1150 parts of stone, and 4-5 parts of water-reducing agent. Alternatively, by weight, the dry material comprises 17.5-52.5 parts of alkali residue internal curing material, 240-250 parts of cement, 52.5-105 parts of fly ash, 590-595 parts of sand, and 1250-1300 parts of stone. Alternatively, by weight, the dry material includes 40-80 parts of alkali slag internal curing material, 560-600 parts of cement, 40-80 parts of fly ash, 40-80 parts of mineral powder, 80-100 parts of silica fume, 340-350 parts of fine sand, 350-360 parts of medium sand, 370-380 parts of coarse sand, and 9-10 parts of water-reducing agent.
10. The concrete according to claim 7, characterized in that, The water-reducing agent includes a polycarboxylate high-performance water-reducing agent.